Patient safety: a culture of openness and supporting staff. Issue 9 (September 2018) - Donaghy, Cathy; Doherty, Rachel; Irwin, Terry
Abstract: The safety of patients and staff are inextricably linked. When healthcare staff are supported by their organization, they are more confident and able to deliver high quality, safe and compassionate care for their patients. Rather than simply 'firefighting' problems they have time for reflection, and the energy and resources to prevent problems from recurring. Confident supported staff are more likely to learn from error. Promoting a culture of openness and learning from mistakes within an organization, rather than a culture of blame and punishment, is of vital importance in allowing this. Such cultures have been slow to develop in the NHS. Poor communication, failure to disseminate information, scapegoating and an unwillingness to learn leads to harm to patients. This article will review how patient safety became a matter of public interest and discuss the effect that adverse events can have on healthcare staff. It describes strategies to support and empower staff to provide the high quality, safe care that they strive for.